A meaning based approach to art therapy - Hlavek, Elizabeth Hadara, author.
1 online resource
Keywords: "A Meaning Based Approach to Art Therapy contextualizes the phenomena of Holocaust artwork for the field of art therapy and uses that canon of artwork to support the inclusion of logotherapy into art therapy theory and practice. The author expounds on a study in which she interviewed surviving Holocaust artists about how they were able to create their artwork while in Nazi captivity. Divided into three sections, the book follows the chronological order of her inquiry. It first presents theory, then research, and ends with implications for the practice of art therapy. The research section includes the process and results of the phenomenological inquiry. It addresses how art-making during the Holocaust allowed captive artists to: provide witness; leave a legacy; and retain their humanity. In the final section, the author shows how art therapists can use concepts from her study to support the progress of their clients. She advocates for the application of logotherapy, an existential philosophy that emphasizes finding meaning to facilitate healing and personal growth. Practicing art therapists and students of art therapy will find this book to be an excellent resource in logotherapy for art therapists, an updated perspective on existentialism, and a contemporary examination of phenomenology"--